The sub‐classification of type B2 vessels according to the magnifying endoscopic classification of the Japan Esophageal Society. Issue 1 (20th August 2019) - Tanaka, Ippei; Hirasawa, Dai; Saito, Hiroaki; Matsuda, Tomoki; Nakahori, Masato; Maeda, Yuki; Okuzono, Toru; Suzuki, Kenjiro; Igarashi, Kimihiro; Nawata, Yoshitaka; Ito, Satoshi; Unno, Shuhei; et al.
Abstract : Objectives: Guidelines for magnified endoscopic diagnosis of esophageal squamous cell carcinoma (SCC) have been proposed by the Japan Esophageal Society. Type B1, B2, and B3 reflect increasing tumor invasion depths (within mucosal epithelium or into lamina propria mucosa [T1a‐EP/LPM], into muscularis mucosa or superficial invasion into submucosa [T1a‐MM/T1b‐SM1], and into submucosa [T1b‐SM2], respectively). The diagnostic accuracy of type B1 and B3 is high, but accuracy of type B2 is low. We aimed to improve the diagnostic accuracy of type B2. Methods: We retrospectively reviewed 248 SCC lesions treated with endoscopic submucosal dissection between January 2012 and July 2018 and identified the B2 lesions. The maximum diameter of the area presenting B2 was measured and evaluated in relation to tumor invasion, for which receiver‐operating characteristic (ROC) curves were generated. The optimal area size for distinguishing T1a‐EP/LPM from T1a‐MM or deeper invasion was determined. Results: There were 78 lesions with B2, of which 26 (33%) were T1a‐MM or T1b‐SM1 SCCs. ROC curve analysis indicated that the optimal cut‐off for the target area showing B2 was 4 mm. The invasion depth (EP/LPM: MM/SM1: SM2) of B2 observed in an area with a diameter <4 mm (B2‐Narrow) and those with diameter ≥4 mm (B2‐Broad) was 46:11:1 and 1:15:4, respectively. To predict T1a‐MM or deeper invasion, B2‐Broad had a sensitivity, specificity, positive predictive value, and negative predictive value of 61%, 98%, 95%, and 79%, respectively. Conclusion: The diagnostic accuracy of type B2 was improved by evaluating the area of type B2.